Nigra sum - Casals, Pablo 1876-1973; American Choral Directors Association. National Convention (1993 : Sacramento, California) (Clarence, NY, : Mark Custom Recording Service, INC., 1993)
Conferencia Nacional de la American Choral Directors Association en la que se presenta "Training the boy's voice"
Información tomada de hoja de presentación plegada e inserta
Florida's Singing Sons Boychoir ; Jeffri W. Bantz, conductor
Keywords: MUSICA CORAL; COROS (VOCES DE NIÑOS); CANTO CORAL -- METODOS DE ENSEÑANZA; MUSICA VOCAL; CULTIVO DE LA VOZ